Romantic Modernism Nostalgia in the World of Conservation - Denslagen, Wim (Amsterdam University Press, 2009)
Is it possible for conservationists to approve of the reconstruction of old façades when virtually everything behind them is modern? Should they continue to protect the front façade, when the rest of the historic building has vanished? Is it socially responsible to spend government money on reconstructing a historic building that has been completely destroyed? Can one do such a thing fifty years on? According to reigning ideas in the world of conservation, the answer to all these questions is 'no'. It is felt that building a stage set is dishonest, and rebuilding something that no longer exists is labelled a lie against history. Where does this predilection for honesty originate? And why do people prefer modern architecture to the reconstruction of what has been lost? Perhaps we are witnessing the legacy of Functionalism here, a movement that denounced the building of pseudo-architecture. Functionalism originated in Romanticism, when architects turned their backs on academic formalism and strove to invent a new, rational form of building. This romantic hunger for honesty was adopted by the conservationists, giving rise to a new respect for the authentic art work and a rejection of historicist restorations. Among conservationists too, distaste arose for the cultivation of a harmonious urban image, because an urban image that is maintained artificially 'old' was seen as a form of fraud.